PENGARUH PEMBERIAN JAHE (Zingiber officinale) TERHADAP GLUKOSA DARAH PASIEN DIABETES MELLITUS - Suharto, Idola Perdana Sulistyoning; Lutfi, Erik Irham; Rahayu, Mega Diasty (Universitas Tribhuwana Tunggadewi, 2019)
The objective of this study was to analysis effect of giving ginger (Zingiber officinale) to the blood glukose in patients of diabetes mellitus. The method was one group pretest – posttest design. There were 16 patients of diabetes mellitus who was given ginger (Zingiber officinale). Ginger (Zingiber officinale) was given twice a day for a week The dose of ginger is 50 mg of ginger boiled with 200 ml of water Blood glucose was measured before and after ginger administration. The data was analyzed by wilcoxon signed rank test. Based on wilcoxon signed rank test, obtained result that there was a significant difference (α